Pengaruh Lama Perendaman Dan Metode Pengolahan Tempe Terhadap Sifat Kimia, Mikrobiologi Dan Organoleptik - Dian Oktrianis Buulolo; Yudiono, Kukuk; Susilowati, Sri (BiSTeK Pertanian, 2023)
Tempeh is a traditional Indonesian food made from fermented soybeans with the fungus Rhizopus Oligosporus and has a distinctive aroma. Tempeh contains many nutrients that are beneficial to health because the nutriens are more easily digested, absorbed, and utilized by the body. An important principle in preparing good tempeh is soaking and boiling it. Soaking is used to achive a suitable pH (acidity) for mold growth, namely 3.5-5.2. and boiling is used to soften soybean seeds and inactivate microbes that grow during soaking. The purpose of this study was to see the effect, interaction between soaking time and processing method on the chemical, microbiological and organoleptic properties of tempeh. This study used a Completely Randomized Design (CRD) factorial two factors. Factor I soaking time (12 hours, 18 hours, and 24 hours). Factor II is the tempeh processing method (one time boiling method and the two-time boiling method). Statistical Analysis using Analysis of Variance (ANOVA) with IBM SPSS version 20 and later Duncan Multiple Range Test (DMRT). Organoleptic test using Ranking Test. Soaking duration and processing method had a significant effect on the observed parameters of water content, protein, antioxidants, color and had no significant effect on the parameters of Total Plate Count (TPC) of mold, as well as texture and odor organoleptic tests. Best on the Indonesian National Standart for 12 hour soaking and one time processing/boiling method, the resulting tempeh contains 57,10% water content, 47,25% protein, 0,39% antioxidants, Total Plate Count (TPC) mold 258 CFU/g x 10-1 and organoleptic texture (compact when sliced), color (white evenly all over the surface), and smell/aroma (typical tempeh odor)